PERLINDUNGAN HUKUM TERHADAP KARYAWAN YANG DIRUMAHKAN DALAM PERJANJIAN KERJA WAKTU TIDAK TERTENTU ( PUTUSAN : NOMOR 491 K/PID.SUS-PHI/2017) - Ellert Ellert Ellert; Willy Tanjaya (jurnal.unprimdn.ac.id, 2019)
That, if the Labour Law protects laid-off workers where workers still get full wages during layoffs. This is regulated in section 93 of article 2 letter f of Labour Law Number 13 of 2003 concerning Labor which states that employers are obliged to pay workers' wages, if workers are willing to do the work promised, but employers do not employ either their own mistakes or obstacles that should be avoided Company. But in practice there are still many workers who are laid off without receiving wages and do not know about their own rights and obligations as discussed in the decision Number 491 K / Pdt.Sus-PHI / 2017 where laid-off employees do not get rights and obligations a permanent work agreement during the lay down period. The purpose of this journal is to find out whether permanent work agreement can be laid off or not, to find out the rights possessed by employees during laying off by the company and the suitability of judges' consideration in giving such decisions to employees laid down based on Labour Law Number 13 of 2003 concerning Labor. The study was conducted using normative juridical research methods with secondary data legal material sources in the legislation and decisions and circulars related to employment with the nature of descriptive legal research. Based on the analysis of the results of the study, it can be concluded that the term laying off permanent work agreement can be carried out under conditions where the rights and obligations of workers are required to be fulfilled in accordance with the law.